The Bold, Silent Type: Predictors of Ultrasonic Vocalizations in the Genus Peromyscus - Kalcounis-Rueppell, Matina C.; Petric, Radmila; Marler, Catherine A. (Frontiers in Ecology and Evolution, 2018)
An ongoing question related to the evolution of monogamy is how behavioral traits that characterize individuals in monogamous species evolve, and whether monogamy influences the evolution of these traits. One of the most important models for the study of monogamy in mammals is the California mouse (Peromyscus californicus) that uses ultrasonic vocalizations (USVs) in multiple behavioral contexts, including pair-bonding and courtship. Because the genus Peromyscus has many species that both use USVs and express a variety of mating systems, we were able to examine the relationship among USVs, and other ecological (e.g. xeric habitat), physiological (testosterone), and behavioral (e.g. boldness) traits across species. We measured USVs from seven species at the Peromyscus Genetic Stock Center and derived character traits associated with the species’ ecology, physiology, and behavior from published studies, including those that had used stocks from the Peromyscus Genetic Stock Center. We determined whether there were USV traits that were particular to monogamous species or whether traits other than mating system best predicted USVs. The trait that best predicted USVs was not related to mating system, but rather, species boldness. Bold species produced few aggressive barks (likely a defensive agonistic USV type) at a higher mean fundamental frequency than less bold species. In relation to mating system, the barks in monogamous species were shorter in duration than the barks in non-monogamous species. Our results suggest that boldness of a species has a higher selection on USVs than the species mating system, ecology, or physiology and that selection has acted on agonistic acoustic signals. Because another type of USV, the sustained vocalization or SV type, did not differ among species in spite of mating system differences, and because all species produced bark types, we suggest that the USVs in rodents evolved as general signals that have generally been co-opted for particular functions within the mating system context that differs across species, as opposed to signals that have been shaped by mating system type.